2007
DOI: 10.1084/jem.20070120
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer of inflammation gp130 modulates atherosclerosis in mice and man

Abstract: Liver-derived acute phase proteins (APPs) emerged as powerful predictors of cardiovascular disease and cardiovascular events, but their functional role in atherosclerosis remains enigmatic. We report that the gp130 receptor, which is a key component of the inflammatory signaling pathway within hepatocytes, influences the risk of atherosclerosis in a hepatocyte-specific gp130 knockout. Mice on an atherosclerosis-prone genetic background exhibit less aortic atherosclerosis (P < 0.05) with decreased plaque macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…Chronic infl ammatory diseases such as rheumathoid arthritis are typically associated with an increased CVD risk in patients ( 4,33 ), and chronic infl ammation causally contributes to atherogenesis in vivo in mouse models ( 10 ). On the other hand, plasma levels of several APPs are elevated in patients with atherosclerotic CVD and have been shown to possess a predictive value for future cardiovascular events ( 8,9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic infl ammatory diseases such as rheumathoid arthritis are typically associated with an increased CVD risk in patients ( 4,33 ), and chronic infl ammation causally contributes to atherogenesis in vivo in mouse models ( 10 ). On the other hand, plasma levels of several APPs are elevated in patients with atherosclerotic CVD and have been shown to possess a predictive value for future cardiovascular events ( 8,9 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the subsequent experiment as-(APPs) have been shown to possess a predictive value for future cardiovascular events ( 8,9 ). Recently, it was also demonstrated that eliminating a large part of the hepatic acute phase response (APR) by knocking out the gp130 receptor on hepatocytes confers signifi cant protection from atherosclerosis, indicating that APP might mechanistically contribute to the atherosclerotic process ( 10 ). Furthermore, infl ammation impacts on HDL metabolism resulting in accelerated HDL catabolism and substantial remodeling of the HDL particle (11)(12)(13), making it likely that these changes might translate into altered in vivo RCT.…”
Section: In Vivo Reverse Cholesterol Transport Studiesmentioning
confidence: 99%
“…38 Polymorphisms of IL-6ST significantly increase the risk of coronary artery disease and myocardial infarction in humans. 39 CNVs at Chr5:55326203 were associated with apoB concentration in NPHS-II, and this association was replicated in the NFBC1966 cohort.…”
Section: Discussionmentioning
confidence: 71%
“…The subsequent dimerization of two gp130 proteins activates the intracellular pathways, resulting in the induction of the acute phase response [8,9]. Soluble forms of IL-6R (sIL-6R) also trigger gp130 dimerization and signalling when complexed with IL-6 [10].…”
Section: Introductionmentioning
confidence: 99%